A computational model of first language acquisition - Satake, Nobuo (Singapore ; New Jersey : World Scientific, 1990)
Introduction; Phenomena in language acquisition and primary data; Learnability theory; BUD and other computational models; The whole constitution of BUD; BUD's category-formation/Integration/Disruption mechanism; Comparison between language phenomena and BUD's behavior; Order mode and production mode; Final remarks.
Revision of the author’s thesis (doctoral--University of Tokyo, 1988) under title: First language acquisition as problem solving.
Includes bibliographical references (p. 175-183) and indexes.
Keywords: Language acquisition; Language acquisition -- Data processing